Analysis of LMS Implementation Success Based on Information System Success and End-User Computing Satisfaction Models - Rahmat Pambudi; Berlilana Berlilana; Giat Karyono (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2025)
A learning Management System (LMS) is critical because it can help improve learning quality and efficiency. Therefore, organizations need to evaluate their performance and utilization. The objective of this study is to evaluate the success of the LMS Onclass implementation using Combination the Information System Success Model (ISSM) and End User Computing Satisfaction (EUCS). This study's data collection approach was a quantitative survey. The population consisted of all students in the Faculty of Engineering and Science at the Muhammadiyah University of Purwokerto, with a total of 1022 using the Onclass. The researcher used data from active students in semesters 1, 3 and 5 with a total of 534 data. The data collection technique was conducted non-test through a questionnaire to assess the success of LMS implementation based on the ISSM and EUCS models. After collecting the data, the next step is to process it using the SEM-PLS multivariate analysis technique, which includes validating the measurement model as well as the structural model. The study's findings revealed that the respondents' data were validated and reliable. The test was then performed, and it was discovered that all hypotheses were accepted, indicating that the factors had a positive and significant influence